Facilitators’ perspective towards implementation of Competency Based Medical Education (CBME) in a Government Medical College in Delhi: a cross-sectional study - Ghurumourthy Dhandapani; Sanjeev Kumar; Sunanda Gupta; Shveta Lukhmana (Discover Education)
Abstract Introduction Competency-Based Medical Education has emerged as a transformative approach to medical education worldwide. It focuses on the overall development of trainee physicians to ensure effective and safe patient care. Objectives To evaluate faculty members’ perspectives on Competency-Based Medical Education and identify perceived challenges for its implementation in a medical college in Delhi. Methods A cross-sectional study was conducted in July 2022 among 127 faculty members of Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi. Data were collected using a validated self-developed questionnaire (Cronbach's alpha: 0.85). Results The median age of the faculty members was 42 years, with a median teaching experience of 10 years. Ninety-one percent of faculty members were aware of Competency-Based Medical Education, and 88% believed it to be superior to the previous curriculum. Integrated teaching (62%) and early clinical exposure (55%) were identified as the most anticipated benefits. Faculty members cited infrastructural deficits (93%) and competing time demands and priorities (85%) as major barriers to implementation. Conclusion To address the challenges, the National Medical Commission should ensure the availability of sufficient infrastructure and provide regular training programs for faculty members.